Protective effect of antioxidants against retinal injury induced by infrared radiation - Saad Elabrak, Eman; Said Mohamed, Kamilia; Sayed El-Nagdy, Mohamed (International Journal of Engineering and Technology, 2019)
The aim of the work is to evaluate the effect of infrared radiation on retinal rabbit rhodopsin and the protecting role of different antioxidants. NewZealand albino rabbits were exposed to infrared radiation 10 minutes direct or fractionated into 5 settings (2 minutes every day), with and without omega-3, Ginko Biloba extract and Grape seed extract as antioxidants supplementation. The rhodopsin has been extracted after decapitation of rabbits, total antioxidant capacity (TAC), and Fourier infrared spectroscopy (FTIR) of bleached rhodopsin was investigated. The data indicated that very high significant decrease (pË‚0.001) in the total antioxidant capacity after exposure to IR for 10 minutes direct or fractionated and changes in the spectral fingerprint region. After treating the rabbits with antioxidants, there were improvement in TAC and matched spectral fingerprint region with control. It may be concluded that the antioxidants omega-3, Ginko Biloba extract and Grape seed extract can protect retinal rhodopsin from oxidative stress that takes place after exposure to infrared radiation. The direct dose of infrared radiation leads to more damage than fractionated dose on retinal rhodopsin.Â Â